Association of the anti-tuberculosis drug rifampicin with a PAMAM dendrimer - Bellini, Reinaldo G.; Guimarães, Ana P.; Pacheco, Marco A.C.; Dias, Douglas M.; Furtado, Vanessa R.; Alencastro, Ricardo B. de; Horta, Bruno A.C. (Journal of Molecular Graphics and Modelling, 2015)
The association of the anti-tuberculosis drug rifampicin (RIF) with a 4th-generation poly(amidoamine) (G4-PAMAM) dendrimer was investigated by means of molecular dynamics simulations. The RIF load capacity was estimated to be around 20 RIF per G4-PAMAM at neutral pH. The complex formed by 20 RIF molecules and the dendrimer (RIF20-PAMAM) was subjected to 100 ns molecular dynamics (MD) simulations at two different pH conditions (neutral and acidic). The complex was found to be significantly more stable in the simulation at neutral pH compared to the simulation at low pH in which the RIF molecules were rapidly and almost simultaneously expelled to the solvent bulk. The high stability of the RIF-PAMAM complex under physiological pH and the rapid release of RIF molecules under acidic medium provide an interesting switch for drug targeting since the Mycobacterium resides within acidic domains of the macrophage. Altogether, these results suggest that, at least in terms of stability and pH-dependent release, PAMAM-like dendrimers may be considered suitable drug delivery systems for RIF and derivatives.
Keywords: Computer simulation; Molecular dynamics; Dendrimer; PAMAM; Rifampicin; Drug delivery